Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1465-9921-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of the outcomes and costs of initiating maintenance therapies in patients with moderate exacerbations of COPD

Abstract: BackgroundThere are limited data describing patients with moderate COPD exacerbations and evaluating comparative effectiveness of maintenance treatments in this patient population. The study examined COPD patients with moderate COPD exacerbations. COPD-related outcomes were compared between patients initiating fluticasone propionate-salmeterol 250/50 mcg (FSC) vs anticholinergics (ACs) following a moderate COPD exacerbation.MethodsThis retrospective observational study used a large administrative claims databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
(16 reference statements)
1
6
1
Order By: Relevance
“…Similar high prescription rates of ICS/LABA in COPD patients have been found in previous studies [ 5 , 6 ] and lower rates in others [ 12 , 13 ]. Although the use of ICS/LABA is recommended in subgroups of COPD patients, to our knowledge, no one has described the characteristics of patients who are prescribed this combination by their GP in real clinical practice.…”
Section: Discussionsupporting
confidence: 88%
“…Similar high prescription rates of ICS/LABA in COPD patients have been found in previous studies [ 5 , 6 ] and lower rates in others [ 12 , 13 ]. Although the use of ICS/LABA is recommended in subgroups of COPD patients, to our knowledge, no one has described the characteristics of patients who are prescribed this combination by their GP in real clinical practice.…”
Section: Discussionsupporting
confidence: 88%
“…This is in-line with our meta-analysis results showing that there was no statistically significant difference between LABA+ICS and LAMA in short-term treatment. In longer-term observational studies, LABA+ICS proved more effective at reducing exacerbations than LAMA 32 33 ; however, in our meta-analysis there was no statistically significant difference between the two treatments in the long-term, though LABA+ICS was ranked higher than LAMA in SUCRA analysis. With a variable follow-up period, up to 1 year with a median of 20 weeks, Chatterjee et al 34 found triple therapy significantly more effective at reducing exacerbations than LAMA.…”
Section: Discussioncontrasting
confidence: 73%
“…Dalal et al 31 (n=4150) found that the number of exacerbations resulting in outpatient visits or rehospitalisation was no different between patients taking LABA+ICS and those taking LAMA within 30 days of an initial COPD-related hospitalisation. Dalal et al 32 (n=2849) found that in the 1-year period following a moderate exacerbation, patients taking LABA+ICS experienced a significantly lower risk of exacerbation than those taking LAMA. Dalal et al 33 (n=4001) similarly found a lower risk of exacerbation and lower exacerbation-related hospitalisation rates in patients with COPD with comorbid depression/anxiety taking LABA+ICS compared with those taking LAMA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the prevalence of diagnosis and procedure codes, as well as healthcare utilization data commonly used to define COPD and AECOPD events, were tabulated for the observation period. Based on the research team's expertise in data related to COPD, previously published algorithms [19][20][21][22][23][24][25] were modified to develop separate algorithms to identify "moderate" and "severe" AECOPD events in administrative data. Of the potential AECOPD events identified with the utilization-based algorithms, random samples of 550 (300 moderate and 250 severe) were selected for detailed medical chart review to validate whether the potential AECOPD was a true event.…”
Section: Study Outcomes Baseline Characteristics and Algorithm Developmentmentioning
confidence: 99%